WHEAT/ICARDA analysis and outreach enables government policies that developed the Moroccan national seed sector, adding 300 new seed businesses - CGIAR Research Program on Wheat (2020)
The 2019 publication of the results of a milestone WHEAT/ICARDA-led 2013 seed sector survey -- coupled with high-level workshops, meetings and discussions with stakeholders --helped shift the political vision in Morocco, leading to several major changes introduced as part of the Green Morocco Plan that have revamped seed business in the country, including the establishment of 300 new seed businesses.